Epidemiological profile of Covid-19 cases and deaths in a reference hospital in the state of Goiás, Brazil - da Silva Oliveira, Gabriela Larissa; Neves Jesus, Rafael; Ferreira Dias, Pollyana; Magalhães de Brito Alvares, Laize Evelyn; Nepomuceno, Ana Carolina; Dourado Nóbrega Sakai, Lívia; Daher, Marcelo Cecilio; Nascimento Silva, Osmar; Hungria Pinto, Emerith Mayra (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
The pandemic caused by the Coronavirus 19 (Coronavirus disease 2019, COVID-19) killed countless people in 2020 and it arrived in Brazil in mid-February from the same year. It spread quickly, through its facilitated form of transmission by droplets of saliva, coughing, sneezing and contaminated surfaces. Several studies have indicated that male people over 60 years of age with comorbidities such as diabetes mellitus, chronic kidney disease, cardiovascular disease and/ or chronic lung diseases had higher rates of progression to Severe Acute Respiratory Syndrome and greater vulnerability to death. In this sense, this study aimed to describe the clinical and epidemiological profile from suspected and confirmed cases of COVID-19 in a hospital in the city of Anápolis, in the State of Goiás, Brazil, from March to December 2020. A total of 1,170 patients were included in this study, with 54.8% of the patients admitted with symptoms of COVID-19 were women (46.9%) aged between 30 and 59 years old. In addition, it was noted that 11.5% of these patients had some type of comorbidities. Furthermore, the data revealed that 82.2% of the laboratory-confirmed patients who died had comorbidities, most of them men (57%), and from the total of 68.5% had two or more comorbidities, with cardiovascular origin being the most frequent reaching 77.5% from the sample. Thus, it was concluded that the clinical-epidemiological profile of suspected and confirmed patients for COVID-19 in this research was characterized by the majority of female patients between 30 and 49 years of age, although most confirmed cases and deaths occurred in men older than 60 years of age. Most confirmed patients had two or more comorbidities, most of them of cardiovascular origin, followed by metabolic syndromes, lung diseases and others. KEY WORDS: COVID-19; epidemiology; comorbidity.